Causal relationship between sarcopenia and rotator cuff tears: a Mendelian randomization study - Yang, Dongmei; Li, Zheng; Jiang, Ziqing; Mei, Xianzhong; Zhang, Daguang; Wei, Qiushi (Frontiers in Endocrinology, 2024)
Background Sarcopenia and rotator cuff tears are common among elderly patients. However, the role of sarcopenia in the management of rotator cuff tears has been often overlooked. This study aimed to elucidate the effects of sarcopenia-related traits on rotator cuff tears. Methods Two-sample Mendelian randomization (MR) analyses based on genome-wide association study data were used to evaluate the causal relationships among appendicular lean mass (ALM), usual walking pace, low hand grip strength, and rotator cuff tears. Multivariate Mendelian randomization (MVMR) analyses were used to evaluate the direct effects of each muscle trait on the causal relationship. Results Univariate MR analysis showed that ALM and usual walking pace were causally related to rotator cuff tears (odds ratio (OR) = 0.895; 95% confidence interval (CI), 0.758-0.966, P<0.001 and OR = 0.458, 95% CI, 0.276-0.762, P = 0.003, respectively), and there was no evidence of causality between low hand grip strength and rotator cuff tears (OR = 1.132, 95% CI, 0.913-1.404, P = 0.26). MVMR analysis confirmed the causal effects of ALM and walking pace on rotator cuff tears (OR = 0.918, 95% CI, 0.851-0.990, P = 0.03 and OR = 0.476, 95% CI, 0.304-0.746, P = 0.001, respectively). Conclusion A causal genetic relationship exists between sarcopenia and rotator cuff tears. Sarcopenia-related traits including low muscle mass and physical function, increase the risk of rotator cuff tears. These findings provide new clinical insights and evidence-based medicine to optimize management of rotator cuff tears.